The Effect of Compound Exercises with Assistive Devices on Developing Static and Dynamic Visual Ability and the Skill of Underhand Serving in Volleyball for Female Students (Damu Journal of Sport Sciences, 2025)
The aim of the research is to prepare compound exercises with assistive devices to develop static and dynamic visual ability and develop underhand serve in volleyball for female students. It is also to identify the effect of compound exercises with assistive devices on developing static and dynamic visual ability in female students.The researchers used the experimental method with a two-group equivalent design, as it is the most appropriate and closest to solving the research problem. The research population included (27) third-year female students in the College for Girls / Department of Physical Education and Sports Sciences / University of Kufa for the academic year (2024-2025). One of the researchers' most important conclusions was that the use of compound exercises using assistive devices significantly impacted the development of the skills studied in the experimental group. Furthermore, the superiority of compound exercises using assistive devices and their effectiveness over the curriculum followed in the lesson on the level of performance in the skills (under study) in volleyball was evident. Furthermore, the experimental group outperformed the control group in the post-tests (development of the visual abilities under study, technical performance, and accuracy of the skill of the underhand serve in volleyball.